Sistema web de historias clínicas electrónicas para la gestión de pacientes ambulatorios en la Clínica San Felipe, Lima-2023 - Caicedo Saavedra, Jesús (2024)
The main objective of this work was to “Develop and Implement a Web System1 of Electronic Medical Records2 for the Management of Outpatients at the San Felipe Clinic. The study is of an applied type, since the implementation introduced a change in the way clinical records are controlled in said health center; with a quasi-experimental design, adopting agile methodologies such as XP3 and Scrum4, both of which are validated and recognized tools in the field of software development engineering. The hypotheses were validated and contrasted, and indicators were evaluated, showing an improvement in the comparative percentage of paper usage, with only 10.57% of the total number of sheets previously used. There were also improvements in the time to obtain medical records, by 92.41%, and in the time to obtain prescribed medications, by 77.6%. In addition, a usability survey was conducted using the System Usability Scale (SUS), obtaining a score of 77.17, surpassing the threshold of 68 points, which is what this standard indicates for being considered acceptable and successful, thus achieving the set objectives. These findings demonstrate the feasibility and effectiveness of the implemented system, as well as the need to transition to electronic systems for more efficient medical care